Are face transplant candidates choosing autonomously? A preliminary method to evaluate autonomous choosing in psychosocial and bioethical assessments - Farías-Yapur, Anneke (Frontiers in Transplantation, 2024)
This report proposes a framework for evaluating the validity of informed consent and autonomy in face-transplant candidates, taking into account the risk of depression and noncompliance. Traditional factors like decisional capacity, disclosure, comprehension, voluntariness, and agreement are insufficient for assessing valid informed consent in individuals whose self-worth relies on public perception, potentially leading to self-harm if societal worth is undermined. Reliance on self-esteem, rather than inherent personal value, poses risks of depression, poor treatment adherence, and deferential vulnerability. We suggest a qualitative analysis of self-worth, self-esteem, self-trust, and self-respect to better assess the autonomy of face-transplant candidates in their decision-making process.